Greek and Latin Roots Part I - Latin - Smith, Peter (Open textbook library., 2016)
Greek and Latin Roots: Part I - Latin is part one of a two part series. This series examines the systematic principles by which a large portion of English vocabulary has evolved from Latin and (to a lesser degree) from Greek. This book focuses on Latin roots. A link to the second part focusing on the Greek roots can be found below. Part I will try to impart some skill in the recognition and proper use of words derived from Latin. There is a stress on principles: although students will be continually looking at interesting individual words, their constant aim will be to discover predictable general patterns of historical development, so that they may be able to cope with new and unfamiliar words of any type that they have studied. They will be shown how to approach the problem by a procedure known as “word analysis,” which is roughly comparable to the dissection of an interesting specimen in the biology laboratory. The text assumes no previous knowledge of Latin, and does not involve the grammatical study of this language—except for a few basic features of noun and verb formation that will help students to understand the Latin legacy in English. Although there will be some attention paid to the historical interaction of Latin with English, this text is definitely not a systematic history of the English language. It focuses on only those elements within English that have been directly or indirectly affected by this classical language. In order to provide the broadest possible service to students, the text emphasizes standard English vocabulary in current use. The more exotic technical vocabulary of science and medicine can be extremely interesting, but is explored in only summary fashion. Nevertheless, this text should be of considerable value, say, to a would-be botanist or medical doctor, if only by providing the foundation for further specialized enquiry.